2011
DOI: 10.1016/j.suronc.2010.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Clinico-pathologic features of primary melanoma and sentinel lymph node predictive for non-sentinel lymph node involvement and overall survival in melanoma patients: A single centre observational cohort study

Abstract: Dec 9. Clinico-pathologic features of primary melanoma and sentinel lymph node predictive for nonsentinel lymph node involvement and overall survival in melanoma patients: a single centre observational cohort study. Quaglino P, Ribero S, Osella-Abate S, Macrì L, Grassi M, Caliendo V, Asioli S, Sapino A, Macripò G, Savoia P, Bernengo MG.You may download, copy and otherwise use the AAM for non-commercial purposes provided that your license is limited by the following restrictions:(1) You may use this AAM for non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 42 publications
4
36
0
1
Order By: Relevance
“…2,11,12 To test this notion, we further selected only those patients from our original low-risk group (nonulcerated thin [2 mm] tumors) who had at least 3 SLN harvested, of which only 1 was positive for metastasis ( Figure 4). Remarkably, among those age \60 years, CLND significantly reduced risk of death from melanoma (P = .003).…”
Section: Resultsmentioning
confidence: 99%
“…2,11,12 To test this notion, we further selected only those patients from our original low-risk group (nonulcerated thin [2 mm] tumors) who had at least 3 SLN harvested, of which only 1 was positive for metastasis ( Figure 4). Remarkably, among those age \60 years, CLND significantly reduced risk of death from melanoma (P = .003).…”
Section: Resultsmentioning
confidence: 99%
“…Many studies have established the role of younger age, greater Breslow thickness, ulceration, and tumour mitotic rate in predicting SLN metastases [3][4][5] .…”
Section: Introductionmentioning
confidence: 99%
“…However, statistical data reviewed from the literature on these factors are still very poor so that currently none of these parameters can give a safe a reliable prognostic indication on NSLNs status. Previous studies have shown that several characteristics of deposits of metastatic melanoma in SLNs correlate with the presence of tumour in NSLNs in subsequent CLND specimens [17,21-24]. In our study, the microanatomic features of the SLNs metastasis, particularly the tumour penetrative depth of the deposit (according with Starz classification) and several clinic-pathologic data were analyzed looking for a predictive marker for NSLN involvement.…”
Section: Discussionmentioning
confidence: 99%
“…As reported in literature, only the 14%-18% of positive patients will harbour further disease in the affected basin [14-17]. Only patients with secondary involvement in NSLNs find benefit in a CLND while a large percentage of patients (NSLNs negative) will increase only the morbidity rate due to this surgical procedure [18].…”
Section: Discussionmentioning
confidence: 99%